A soluble, high-affinity, interleukin-4-binding protein is present in the biological fluids of mice. - Fernandez-Botran, R (1990)
Cytokines such as interleukin 4 (IL-4) play a key role in the regulation of immune responses, but little is known about how their multiple activities are regulated in vivo. In this report, we demonstrated that an IL-4-binding protein (IL-4BP) is constitutively present in the biological fluids of mice (serum, ascites, fluid, and urine). Binding of 125I-labeled IL-4 to the IL-4BP is specific and saturable and can be inhibited by an excess of unlabeled IL-4 but not IL-2. The IL-4BP binds IL-4 with an affinity similar to that reported for the cellular IL-4 receptor (Kd approximately 7 x 10(-11) M) and has a molecular mass of 30-40 kDa and pI values of 3.6-4.8. IL-4BP-containing biological fluids or purified IL-4BP competitively inhibit the binding of 125I-labeled IL-4 to mouse T or B cells and inhibit the biological activity of IL-4 but not IL-2. The serum levels of IL-4BP in severe combined immunodeficiency (SCID) mice are lower than those of normal mice. The above findings suggest that IL-4BP plays an important immunoregulatory role in vivo.